Body Mass Index and Risk of Rheumatoid Arthritis: A Meta-Analysis of Observational Studies. Issue 8 (February 2016) - Feng, Jian; Chen, Qi; Yu, Feifei; Wang, Zhiyong; Chen, Shuqi; Jin, Zhichao; Cai, Qing; Liu, Yu; He, Jia
Abstract : Abstract: Although many epidemiological studies have investigated the association between body mass index (BMI) and risk of rheumatoid (RA), the results have been inconsistent. Therefore, we performed a dose-response meta-analysis to quantify the dose-response association between BMI and RA risk. We systematically searched PubMed, Embase, and Web of Science databases and reference lists of articles for relevant studies published before August 2014 using terms related to BMI and RA. Fixed or random-effects models were used to estimate the pooled relative risk (RR) with 95% confidence interval (CI). Several subgroup analyses, sensitivity analyses, and publication bias tests were performed to explore potential study heterogeneity and bias Thirteen studies involving 400, 609 participants and 13, 562 RA cases were included. The RR of RA was 1.21 (95% CI: 1.02–1.44) for obesity, 1.05 (95% CI: 0.97–1.13) for overweight. The risk of RA increased by 13% (RR: 1.13; 95% CI: 1.01–1.26) for every 5 kg/m 2 increase in BMI. The subgroup analyses showed a positive association between BMI and RA risk only in women with an RR of 1.26 (95% CI: 1.12–1.40) for obesity and 1.12(95% CI: 1.07–1.18) for every 5 kg/m 2 increase in BMI. Also, an increased risk of RA was found in sero-negative subgroup with an RR of 1.47 (95% CI: 1.11–1.96) for obesity and 1.21 (95% CI: 1.06–1.39) for every 5 kg/m 2 increase in BMI. There is evidence that obesity is a risk factor for developing of RA. Furthermore, the positive association between BMI and RA risk may be stronger among women than men.